The sum of three consecutive even integers is 36. Let x represent the first integer, x + 2 represent the second integer, and x + 4 represent the third integer.Which equation can be used to find the first integer?A)3x = 2x + 6B)3x + 6 = 36C)3x + 36 = 2x + 6D)2x + 6 = 36

Accepted Solution

Letx------>  the first even integerx+2---->the second even integer x+3---->the third even integer we know that[tex]x+(x+2)+(x+4)=36[/tex] -----> equation that represent the situationsolve for xCombine like terms in the left side[tex](x+x+x)+(2+4)=36[/tex][tex]3x+6=36[/tex]thereforethe answer is the option B[tex]3x+6=36[/tex]